Atomically Structural Regulations of Carbon‐Based Single‐Atom Catalysts for Electrochemical CO2 Reduction. Issue 8 (29th June 2021) - Han, Shu‐Guo; Ma, Dong‐Dong; Zhu, Qi‐Long
Abstract: The electrochemical carbon dioxide reduction reaction (CO2 RR) converting CO2 into value‐added chemicals and fuels to realize carbon recycling is a solution to the problem of renewable energy shortage and environmental pollution. Among all the catalysts, the carbon‐based single‐atom catalysts (SACs) with isolated metal atoms immobilized on conductive carbon substrates have shown significant potential toward CO2 RR, which intrigues researchers to explore high‐performance SACs for fuel and chemical production by CO2 RR. Especially, regulating the coordination structures of the metal centers and the microenvironments of the substrates in carbon‐based SACs has emerged as an effective strategy for the tailoring of their CO2 RR catalytic performance. In this review, the current in situ/operando study techniques and the fundamental parameters for CO2 RR performance are first briefly presented. Furthermore, the recent advances in synthetic strategies which regulate the atomic structures of the carbon‐based SACs, including heteroatom coordination, coordination numbers, diatomic metal centers, and the microenvironments of substrates are summarized. In particular, the structure‐performance relationship of the SACs toward CO2 RR is highlighted. Finally, the inevitable challenges for SACs are outlined and further research directions toward CO2 RR are presented from the perspectives. Abstract : This review summarizes the recent advances on the atomically structural regulations of the carbon‐based single‐atom catalysts (SACs), including the coordination structures of the isolated metal centers and the local microenvironments. Meanwhile, the influences of the atomic structures of SACs on their catalytic performance for electrochemical CO2 reduction are highlighted.